Attention or at ease adult children's perspective on their military fathers' parenting style - Diamante, Jewel A.; Agustin, Estrella R. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
This research describes the parenting styles of military officers from the perspective of their now-adult children. Thirty respondents were asked to recall the interactions they had with their fathers when they were in high school through storytelling. Likert scales were used to identify their fathers' degree of parenting dimensions. Qualitative data was organized using themes, while mean scores were used to identify descriptive ratings. The respondents generally found their fathers to be slightly warm as opposed to being hostile, slightly restrictive as opposed to being permissive, and equally calm and anxious. Paternal warmth was described by children's accounts of how their fathers expressed affection, how they made their children feel that they are an important part of their fathers lives, nonhostile reactions of fathers to children's undesirable actions, and showing approval to children's desirable actions. On the other hand, hostility was described by fathers nonexpression of affection, not making children feel that they are important to their fathers, hostile reactions to undesirable actions, and not showing approval and affirmation for good behaviors. Restrictiveness was described using children's report of their fathers' rules with regard to going out and staying out late, personal values and accomplishments, social relationships, and household matters. Permissive rules were in the areas of staying/ going out and social relationships. Anxious involvement was qualitatively described by children citing fathers behaviors and restrictions that were perceived to be overly protective and solicitous of their children. Calm involvement of fathers was described by children who shared that their fathers did not show behaviors or impose restrictions that would suggest that they were overly involved in the children's affairs. The other significant aspects of concerns of military fathers in relation to their children's lives include the following: (1) frequency of time spent by the fathers with their children; (2) fathers having the secondary role after mothers in the creation and implementation of rules and sanctions; (3) partiality of the fathers' treatment of their children and(4) financial limitations of the families. Overall, most respondents have now found their fathers' parenting styles desirable and actually attribute whatever success they currently have in life to the way they were reared by their fathers.
Thesis (Master of Family Life and Child Development)--University of the Philippines Diliman, June 2016.
Keywords: Parenting -- Philippines; Fathers and daughters -- Philippines